Deletion of Flv3A facilitates long-term H2 photoproduction in diazotrophic Anabaena sp. PCC 7120 - He, Meilin; Santana-Sánchez, Anita; Tóth, Gábor Szilveszter; Ermakova, Maria; Collard, Darius; Kosourov, Sergey; Allahverdiyeva, Yagut (WILEY, 2025)
Molecular hydrogen (H2) is a promising energy carrier, and its production by photosynthetic microorganisms holds substantial potential for advancing renewable energy generation. The nitrogenase-mediated H2 production using heterocyst-forming cyanobacteria represents a promising approach, as the process utilizes light energy and photosynthetic reductants while being naturally protected from O2-rich environments by its restriction to microoxic heterocyst cells. We investigated the impact of deleting the vegetative cell-specific flavodiiron protein, Flv3A, on the long-term H2 photoproduction of the model heterocyst-forming cyanobacterium Anabaena sp. PCC 7120. The H2 photoproduction response was evaluated under varying atmospheric conditions, with or without N2 and O2, and compared to the triangle hupL mutant, which is deficient in the large subunit of uptake hydrogenase, and the triangle hupL/flv3A double mutant. Unlike the Delta hupL mutant, H2 photoproduction in Delta flv3A is not enhanced by increased nitrogenase activity or high accumulation of sugars in cells. Our results suggest that the absence of the vegetative cell-localized Flv3A positively affects H2 photoproduction in heterocysts by simultaneously downregulating hupL expression and enhancing the O2 tolerance of nitrogenase via a yet unexplored mechanism. These findings advance our understanding of nitrogenase-driven H2 production and provide a new strategy to address key limitations in long-term photobiological H2 production.